THE ICEMAN COMETH: ALCOHOLISM AS MODE OF MALADJUSTMENT IN FACING GRAYING TIME PROBLEMS - Dyah Eko Hapsari (ISSN)
Being old brings about many consequences which are mostly negative. Viewed as physically weaker, mentally unstable, and socially dependent are driven to a hard time where they need to cope with those bad labels. Successfull geriatrics can pass through the hard time by maintaining their self esteem to meet with self concept. However, not all geriatrics can come to such situation. They are trapped with the labels addressed to them and fail in maintaining the self esteem. Sometimes, alcoholism becomes one of the outlets to lessen the burdens. The Iceman Cometh is the portrayal of how the aged characters run away from bitter reality to alcoholism which is considered the best way to lessen their psychological burden. Therefore, the mode of maladjustment in facing problems which is best viewed from psychological perspective becomes an outstanding facet of the play.